PC Controlled Multichannel Timer Schedular (Global Journals of Research in Engineering, 2011)
Looking at today's scenario throughout the world we get to see how fast paced our life has become and time is the most valuable thing. Communication media have played an important role in bringing theworld closer.The system deals with customized industrial process manager at the vicinity of personal computer. For this we are using one of the most widely available technologies namely wireless communication.In any manufacturing process there are lots of valves
Keywords: Communication; technologies; intervals